Construction of Durvalumab/carbon nanotube/PEI/aptamer-siRNA chimera for the immunotherapy of hepatocellular carcinoma. (1st March 2022) - Qiang, Niu; Wei, Lv; Tao, Yan; Jin, Wang; Bin, Yan; DingHua, Zhou
Abstract: Immunotherapy is the most promising treatment for hepatocellular carcinoma (HCC). However, the immunosuppressive microenvironment and necrosis limit its therapeutic effectiveness. Carbon nanotubes (CNTs) have good tissue permeability and can penetrate tumor necrosis area. Here we constructed a Durvalumab/CNT/PEI/aptamer-siRNA chimera (chimera/Durmab/CNT) nanoparticles for the immunotherapy of HCC. In vivo and in vitro experiments showed that aptamer-siRNA chimeras could specifically bind HCC cells and inhibit the triggering receptor expressed on myeloid cells-2 (Trem2) expression, but had no effect on Trem2 expression in normal liver and lung. Transmission electron microscope results showed that the CNT/PEI nanoparticles were 20–30 nm in diameter and 200–350 nm in length. Dense PEI attachment can be observed on CNTs. CNT/PEI nanoparticles could control the sustained release of Durvalumab for 48 h. In vitro experimental results showed that chimera/Durmab/CNT could increase the proportion of T cells and CD8 + T cells, and then promote the apoptosis of HepG2 cells, and the therapeutic effect was superior to aptamer/Durmab/CNT and Durmab/CNT. We constructed a tumor-bearing mouse model, and the results showed that chimera/Durmab/CNT significantly inhibited the growth of transplanted tumor, and the volume and proliferation was further reduced in the chimera/Durmab/CNT group compared with the aptamer/Durmab/CNT group. T cells and CD8 + T cells infiltration, and HCC cell apoptosis were significantly increased in the chimera/Durmab/CNT group. In conclusion, we constructed a Durvalumab/CNT/PEI/chimera, which can effectively treat HCC by activating anti-tumor immunity.